Anger and it’s management - Pashupati, Mahat; Dev, Sharma Vidya (Journal of Nobel Medical College, 2012)
Anger as an emotional reaction involves both physical and psychological changes in our health. Despite of common emotional reactions, it can create many physical and psychological disturbances and diseases as well. So, information regarding its management is helpful to learn some of the simple skills to control it. There cannot be a single cause of the anger. Heredity factors, home environment, social learning and cultural factors are important factors for its emergence. Behavioral techniques and cognitive restructuring techniques are found to be effective methods in controlling anger reaction if practiced properly and systematically. They are effective only if practicing therapist or psychologist is equipped with these skills. It cannot be done just reading an article in the books. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7282 Journal of Nobel Medical College Vol.1(1) 2011 9-14